Fluid Mixing for Low‐Power 'Digital Microfluidics' Using Electroactive Molecular Monolayers. Issue 10 (27th December 2017) - Maglione, Maria Serena; Casalini, Stefano; Georgakopoulos, Stamatis; Barbalinardo, Marianna; Parkula, Vitaliy; Crivillers, Núria; Rovira, Concepció; Greco, Pierpaolo; Mas‐Torrent, Marta
Abstract: A switchable electrode, which relies on an indium‐tin oxide conductive substrate coated with a self‐assembled monolayer terminated with an anthraquinone group (AQ), is reported as an electrowetting system. AQ electrochemical features confer the capability of yielding a significant modulation of surface wettability as high as 26° when its redox state is switched. Hence, an array of planar electrodes for droplets actuation is fabricated and integrated in a microfluidic device to perform mixing and dispensing on sub‐nanoliter scale. Vehiculation of cells across microfluidic compartments is made possible by taking full advantage of surface electrowetting in culture medium. Abstract : An array of planar indium‐tin oxide electrodes for droplets actuation based on a self‐assembled monolayer terminated with a switchable electroactive anthraquinone group is fabricated. The electrodes are integrated in a microfluidic device to perform mixing and dispensing at sub‐nanoliter scale. Vehiculation of cells across microfluidic compartments is further demonstrated.